PEMERIKSAAN KASUS PIDANA PEMBUNUHAN BERENCANA YANG TIDAK DIDAMPINGI PENASEHAT HUKUM TINGKAT PENYIDIKAN - Shela; Abdul Fickar Hadjar (Reformasi Hukum Trisakti, 2023)
The Criminal Procedure Code (KJUHAP) contains an obligation if a suspect or defendant commits a crime which carries a threat of 5 years, the official at the examination must appoint a legal adviser, but in Decision Number 929/Pid.B/2021/PN.MKS there is still investigators who do not carry out the provisions of the obligation regarding the appointment of legal advisers. The formulation of the problem in this study is the legal consequence of examining a defendant who committed the crime of premeditated murder who was not accompanied by a legal adviser at the investigative level and whether the judge's consideration of not being accompanied was in accordance with Article 56 paragraph (1) of the Criminal Procedure Code. This research is normative juridical using secondary and primary data, qualitative data analysis and deductive conclusions. The results of the research and discussion show that the investigators did not carry out their obligations by presenting legal counsel for the Defendant and the judge's considerations were inconsistent with Article 56 paragraph (1) and the judge did not see any jurisprudence related to the absence of legal counsel for the Defendant.